(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
Rising prices for goods and services affect the financial sector, both in our country and abroad, which determines the relevance of studying this topic. This situation in the capital market entails negative consequences for the growth and development of the economy at the present stage. It reflects not only the financial system, but also affects all spheres of citizens’ lives. This state of affairs in economics is called “inflation”.